A taxonomic and phylogenetic revision of Maorothiini trib. n. from the New Zealand subregion (Coleoptera: Staphylinidae, Staphylininae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2000)
The types of the New Zealand species previously attributed to the genus Othius Stephens and additional material are revised. A phylogenetic analysis including the New Zealand species, all the genera of Othiini from the Holarctic region, several representative taxa of all other staphylinine tribes, and the genus Lathrobium Gravenhorst of the Paederinae as outgroup yielded the following major results: (a) the New Zealand species form a monophylum; (b) Othius Stephens is a Palaearctic genus and not the sister group of the New Zealand species, but the adelphotaxon of the Holarctic monophylum Atrecus Jacquelin du Val + Caecolinus Jeannel + Parothius Casey; (c) a sister group relationship between the New Zealand species and Holarctic Othiini is doubtful, if not unlikely. Therefore, the tribe Maorothiini trib. n. is established to accommodate the New Zealand taxa previously attributed to Othius. The new tribe is attributed to the Staphylininae and distinguished from other tribes of the subfamily. It includes only the type genus Maorothius gen. n., whose designated type species is Othius adustus Broun and whose distribution is apparently confined to the New Zealand subregion. In all, 20 species of Maorothius are distinguished and (re-)described: M. adustus (Broun), comb. n., M. hamifer sp. n., M. setiger sp. n., M. longispinosus sp. n., M. brevispinosus sp. n., M. insulanus sp. n., M. brookesi (Cameron), comb. n., M. hammondi sp. n., M. pubescens sp. n., M. effeminatus sp. n., M. pectinatus sp. n., M. puncticeps (Broun), comb. n., M. coalitus sp. n., M. tridens sp. n., M. volans sp. n., M. dispar sp. n., M. brouni (Steel), comb. n., M. tonsor sp. n., M. torquatus sp. n., and M. solus sp. n. Lectotypes are designated for M. adustus (Broun), M. brookesi (Cameron), and M. brouni (Steel). The phylogenetic affiliations among the species of Maorothius are analyzed, discussed, and figured. Drawings illustrating distinguishing characters and a key to the species are provided. Bionomical and biogeographical data are compiled and mapped, respectively. Keywords Coleoptera, Staphylinidae, Staphylininae, Othiini, Diochini, Staphylinini, Platyprosopini, Maorothiini, Maorothius, Othius, New Zealand, phylogeny, taxonomy, revision, distribution, bionomics, endoparasitism, new tribe, new genus, new species, new combinations, lectotype designations. Nomenclatural Acts adustus (Broun, 1880) (Maorothius), comb. n. hitherto Othius adustus brevispinosus Assing, 2000 (Maorothius), spec. n. brookesi (Cameron, 1952) (Maorothius), comb. n. hitherto Othius brookesi brouni (Steel, 1948) (Maorothius), comb. n. hitherto Gyrohypnus brouni coalitus Assing, 2000 (Maorothius), spec. n. dispar Assing, 2000 (Maorothius), spec. n. effeminatus Assing, 2000 (Maorothius), spec. n. hamifer Assing, 2000 (Maorothius), spec. n. hammondi Assing, 2000 (Maorothius), spec. n. insulanus Assing, 2000 (Maorothius), spec. n. longispinosus Assing, 2000 (Maorothius), spec. n. pectinatus Assing, 2000 (Maorothius), spec. n. pubescens Assing, 2000 (Maorothius), spec. n. puncticeps (Broun, 1894) (Maorothius), comb. n. hitherto Othius puncticeps setiger Assing, 2000 (Maorothius), spec. n. solus Assing, 2000 (Maorothius), spec. n. tonsor Assing, 2000 (Maorothius), spec. n. torquatus Assing, 2000 (Maorothius), spec. n. tridens Assing, 2000 (Maorothius), spec. n. volans Assing, 2000 (Maorothius), spec. n. Maorothius Assing, 2000 (Staphylinidae), gen. n. Maorothiini Assing, 2000 (Staphylininae), trib. n.